ENERGY SAVING HEATING UNITS OF NEW GENERATION - V. V. Korobeynikov; S. S. Tkachenko (Литьë и металлургия)
Modern thermal equipment could and should be energy saving, efficient, safe and environmentally friendly one. The company «TAKHTEH-RUS» LLC (Saint Petersburg) is a modern scientific and production enterprise which develops and produces energy-saving thermal units for wide range of applications.